THE TREATMENT OF ANTERIOR TOOTH CROWDED CASE OF UPPER JAW WITH DENTAL TRANSPOSITION BETWEEN CANINE AND LATERAL INCISOR TOOTH BY FIXED APPLIANCE - Dr.drg. Tita Ratya Utari, Sp.Ort (fdi-ida bppn, 2010)
the aim this paper was to report the success of the treatment of a case of an upper canine transpose with lateral incisor